2022
DOI: 10.1002/app.53137
|View full text |Cite
|
Sign up to set email alerts
|

Dually responsive biodegradable drug releasing 3D printed structures

Abstract: The aim of this study was to develop temperature and pH‐responsive biodegradable 3D printed drug‐releasing constructs using the Digital Light Processing (DLP) printing technique. The printable molecules, named “inks” throughout this study, comprised polyethylene oxide–polypropylene oxide–polyethylene oxide (PEO–PPO–PEO) triblocks and acrylic acid (AAc) that rendered them reverse thermo‐responsive (RTR) and pH‐sensitive, respectively. Additionally, the inks' biodegradability was imparted to them by incorporatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…In this case, the secondary crosslinking of the material with Ca 2+ gave the tablets an active response at different pH values. A pH-sensitive 3D-printed formulation was developed for colon-specific protein release [ 174 ]. For this, they used the digital light processing (DLP) printing technique to co-print constructs based on the reverse thermo-responsive poly (ethylene oxide)/poly(propylene oxide)/poly(ethylene oxide) (PEO–PPO–PEO) triblocks and the pH-responsive acrylic acid to provide them pH sensitivity.…”
Section: Stimulus and Effect On Responsive Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the secondary crosslinking of the material with Ca 2+ gave the tablets an active response at different pH values. A pH-sensitive 3D-printed formulation was developed for colon-specific protein release [ 174 ]. For this, they used the digital light processing (DLP) printing technique to co-print constructs based on the reverse thermo-responsive poly (ethylene oxide)/poly(propylene oxide)/poly(ethylene oxide) (PEO–PPO–PEO) triblocks and the pH-responsive acrylic acid to provide them pH sensitivity.…”
Section: Stimulus and Effect On Responsive Materialsmentioning
confidence: 99%
“…GelMA-filled silicate nanoplatelets containing hMSCs Promotion of the formation, stability, and maturation of vascular vessels in vitro [174] PEG tetrabicyclononyne (Mn ~20,000 Da), diazide-functionalized synthetic peptide Generation of endothelialized 3D vascular networks [206] Hyaluronic acid functionalized with photoisomerized tetra-ortho-methoxy-substituted Azo crosslinked to cyclodextrins Regeneration of functional multi-tissue complex under an external control [208] PCL, lauric acid, and melanin Controlled release of insulin [211] Dihydrazide-modified HA hydrogel Effective, localized delivery of anti-cancer agents [212] PCL impregnated with gold nanoparticles-decorated carbon nanofibers Controlled drug release [215] Chitosan microswimmers Controlled drug release [218] Wool keratin modified with TTFAP and AzA Wound healing and tissue-engineering applications.Antimicrobial activity [221] Alginate-gelatin hydrogels coated with PCL and PDA Controlled release of doxorubicin for cancer therapy [223] CNTs-doped N-isopropylacrylamide (NIPAM) composite hydrogel Biomimetic aortic valve microstructure [224] Gelatin methacryloyl with iron oxide nanoparticles Generation of bioinspired soft robotic systems [213] Nanoclay-incorporated double-network hydrogel with magnetite nanoparticles Magnetic guided movement [214] Humidity PEG bilayers 3D biological studies and tissue engineering [248] Multisomes Domain of synthetic biology and medicine [249] Zein gel in a supporting bath of Carbopol Development of controlled self-assembly biomedical materials [250] Enzymes PEGDA hydrogel with alkaline phosphatase and thrombin Formation of calcified structures and fiber patterns [252] 2-carboxyethyl acrylate added to photocurable resins and derivatized with urease and glucose oxidase On-site determination of urea and glucose [193]…”
Section: Lightmentioning
confidence: 99%
“…In the literature, the last year’s other architectures based on the same polymers as AB/ABA architectures or other polymers are currently under investigation. Moreover, using natural polymers, polypeptides, hydroxyapatite, or clay has contributed much to 3D printing in the last few years [ 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 ].…”
Section: Advances and Applications Of Block Copolymers In 3d/4d Print...mentioning
confidence: 99%
“…It has been shown that the PLA/PCL ratio plays an important role. It has been suggested that these materials can be good candidates for colon protein release formulations [ 111 ].…”
Section: Advances and Applications Of Block Copolymers In 3d/4d Print...mentioning
confidence: 99%